Comparing Patient-Centered Medical Home Implementation in Urban and Rural VHA Clinics: Results From the Patient Aligned Care Team Initiative. Issue 1 (January 2018) - Johnson, Victoria; Wong, Edwin; Lampman, Michelle; Curtis, Idamay; Fortney, John; Kaboli, Peter; Fihn, Stephan; Nelson, Karin
Abstract : Rural Veterans Health Administration (VHA) primary care clinics are smaller, have fewer staff, and serve more rural patients compared with urban VHA primary care clinics. This may lead to different challenges to implementation of the Patient-Centered Medical Home (PCMH) model, the Patient Aligned Care Team, in the VHAs' large integrated health system. In this cross-sectional observational study of 905 VHA primary clinics in the United States and Puerto Rico, we found overall PCMH implementation was greater in rural compared to urban primary care clinics. Urban-rural differences in PCMH implementation may largely be related to clinic organizational factors.